Traditional Pesantren, Parental Involvement, and Santri Well-being: Insights from Pesantren Sunan Pandanaran of Yogyakarta - Jahidin, Asep (UIN Sunan Kalijaga, Yogyakarta, Indonesia, 2023)
The importance of student well-being in the context of positive youth development is widely acknowledged, despite little recognitions regarding what it means for santri to live well in the educational setting of traditional pesantren. “santri well-being” encompasses a dual-faceted composition, encompassing affective elements and life satisfaction of the pesantren students. A kiai or caregivers, not only acting as a prominent religious scholar and charismatic leader, but also assumes a pivotal role as a custodial figure within the contextual fabric of traditional pesantren milieu. The focal point of this research revolves around the examination of santri well-being within the context of Pesantren Sunan Pandanaran. With an educational heritage spanning half a century, it maintains a profound affiliation with Nahdlatul Ulama, the largest Islamic organization in contemporary Indonesia. Situated in Yogyakarta, the pesantren has exhibited substantial progress of education strategies over time, adopting modern innovations while upholding its traditional Sunni values and principles. The research methodology involved the purposive selection of eight informants strategically chosen in accordance with the research objectives. This cohort comprises both students and caregivers affiliated with the pesantren. The findings marked Pesantren Sunan Pandanaran’s swift adaptation to modern educational paradigms while preserving its traditional values. A complex network of parental apparatuses exists to provide care, guidance, and support to santri, encapsulating a range of individuals and roles that collectively contribute to overall well-being and development of students. This complexity is further underscored by the collective commitment of pesantren members to uphold the Sunni theology with a demand on righteous and orthodox belief. Through such dynamic caregiving approaches, the pesantren seeks to strike a balance between tradition-innovation, thus fulfilling its mission to nurture santri well-being and satisfaction within a rich Islamic Sunni tradition.